Heterogeneous Interface Design for Enhanced Sodium Storage: Sb Quantum Dots Confined by Functional Carbon. Issue 7 (16th June 2021) - Qiu, Tianyun; Yang, Li; Xiang, Yinger; Ye, Yu; Zou, Guoqiang; Hou, Hongshuai; Ji, Xiaobo
Abstract: Antimony (Sb) is considered a promising anode material for sodium‐ion batteries due to its high specific capacity and moderate working potential. However, the non‐negligible volume variation leads to the rapid decay of capacity, which hinders the practical application of Sb anode materials. Here, an economical and scalable route with high yield is proposed to obtain Sb ultrafine nanocrystals embedded in a porous carbon skeleton. Notably, the synergetic effect of the heterogeneous structure is maximized by inducing the interfacial coupling SbOC and creating buffering space for the volume effect of Sb. The high‐entropy phase interface creates the doping site breaking the periodicity of atoms and alters the electronic structure, also bridging the slip of intergranular defects. Thus, the electronic conductivity and phase interface structural stability are reinforced. The mechanism of accelerating electron migration at the heterogeneous phase interface is visualized through the density functional theory method, and the mass/charge‐transfer kinetics is analyzed via the calculation of surface‐induced capacitive contribution. Abstract : Antimony (Sb) quantum dots confined by functional carbon are obtained through one‐step carbothermal reduction. The synergetic effect of the heterogeneous structure is maximized by inducing the interfacial coupling SbOC and creating buffering space for the volume effect of Sb, which effectively promotes the sodium‐storage performance of Sb.